NKG2C+CD57+ Natural Killer Cell Expansion Parallels Cytomegalovirus-Specific CD8+ T Cell Evolution towards Senescence - John Heath; Nicholas Newhook; Emilie Comeau; Maureen Gallant; Neva Fudge; Michael Grant (Journal of Immunology Research)
Objective. Measuring NKG2C+CD57+ natural killer (NK) cell expansion to investigate NK responses against human cytomegalovirus (HCMV) and assessing relationships with adaptive immunity against HCMV. Methods. Expansion of NKG2C+CD57+ NK was measured in peripheral blood mononuclear cells (PBMC) from groups distinguished by HCMV and human immunodeficiency virus (HIV) infection status. Anti-HCMV antibody levels against HCMV-infected MRC-5 cell lysate were assessed by ELISA and HCMV-specific CD8+ T cell responses characterized by intracellular flow cytometry following PBMC stimulation with immunodominant HCMV peptides. Results. Median NK, antibody, and CD8+ T cell responses against HCMV were significantly greater in the HCMV/HIV coinfected group than the group infected with CMV alone. The fraction of CMV-specific CD8+ T cells expressing CD28 correlated inversely with NKG2C+CD57+ NK expansion in HIV infection. Conclusion. Our data reveal no significant direct relationships between NK and adaptive immunity against HCMV. However, stronger NK and adaptive immune responses against HCMV and an inverse correlation between NKG2C+CD57+ NK expansion and proliferative reserve of HCMV-specific CD8+ T cells, as signified by CD28 expression, indicate parallel evolution of NK and T cell responses against HCMV in HIV infection. Similar aspects of chronic HCMV infection may drive both NK and CD8+ T cell memory inflation.